2008
DOI: 10.1016/j.ultrasmedbio.2007.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ultrasound Elasticity Imaging (UEI) of Crohn's Disease: Animal Model

Abstract: Inflammation occurs in episodic flares in Crohn's disease, which are part of the waxing and waning course of the disease. Healing between flares allows the intestine to reconstitute its epithelium, but this healing results in the deposition of fibrotic scar tissue as part of the healing process. Repeated cycles of flares and healing often lead to clinically significant fibrosis and stenosis of the intestine. Patients are treated empirically with steroids, with their many side effects, in the hope that they wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 73 publications
0
72
0
Order By: Relevance
“…Colon samples with gradually changed disease conditions will be tested in our future study for further understanding the sensitivity and specificity of PAI on characterizing the intestinal strictures. Although the pulse-echo US did not show significant differences between the samples, US elasticity imaging also under investigation by the authors has demonstrated promising results in distinguishing inflammatory and fibrotic intestinal strictures [22,23].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Colon samples with gradually changed disease conditions will be tested in our future study for further understanding the sensitivity and specificity of PAI on characterizing the intestinal strictures. Although the pulse-echo US did not show significant differences between the samples, US elasticity imaging also under investigation by the authors has demonstrated promising results in distinguishing inflammatory and fibrotic intestinal strictures [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, since hemoglobin and collagen have almost parallel optical spectra in 1300s nm, optical wavelengths within this range produce similar results as the major molecular components in the samples were limited to hemoglobin and collagen. Water component change in the two types of samples was not considered as we did not find diseased conditions correlated to water content change [22,23]. Water content within the sample holder is stringently controlled to be identical for all experiment cases and thereby does not contribute to the difference between the PA images of the samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations